Bulgaria : Financial Sector Assessment Program. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses key findings and recommendations of the Detailed Assessment of Observance on the Basel Core Principles for Effective Banking Supervision on Bulgaria. Within the Banking Supervision Department, the Special Supervision Directorate (SSD) has been assigned multiple activities that go beyond its primary objective of ensuring integrity in the banking sector. The Bulgarian National Bank is not empowered to require a bank to change its internal organization or structure. It is recommended to refocus the activity of the SSD on its core mandate of financial integrity. This recommendation can be achieved by assigning nonsupervisory activities to other Directorates, preferably outside the Banking Supervision Department.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet